Financial institutions management : a risk management approach - Saunders, Anthony, 1949-; Cornett, Marcia Millon (New York : McGraw-Hill/Irwin, 2006)
Focuses on managing return and risk in financial institutions. The text argues that risks faced by financial institutions managers, and the methods and markets through which these risks are managed are becoming similar whether an institution is chartered as a commercial bank, a savings bank, an investment bank, or an insurance company.
Includes index.
oif 26/08/15
Loan
Keywords: Financial institutions -- United States -- Management; Risk management -- United States; Financial services industry -- United States -- Management